Web-based Systems Development: The Influence of Disciplinary Backgrounds on Design Practices - Lang, Michael (Journal of Information and Organizational Sciences, 2009)
Web development teams are multidisciplinary, bringing together designers from a variety of backgrounds. A Web designer’s professional training and education can shape his problem-solving orientation and world view by indoctrinating certain values and conditioning him to think and behave in certain ways. This paper presents an analysis of data gathered across 14 interviews, wherein four distinct orientations were identified: (1) Web development as the design of a functional software application (emphasis on back-end functionality); (2) as the design of an interactive tool (emphasis on ergonomics); (3) as the design of a communicational dialogue (emphasis on audience engagement); and (4) as an extension of branded graphic design (emphasis on visual presentation).